Identification of interaction effects in survey expectations: A cautionary note - Simone Alfarano; Mishael Milaković (Bamberg University, Bamberg Economic Research Group on Government and Growth (BERG), 2010)
A growing body of literature reports evidence of social interaction effects in survey expectations. In this note, we argue that evidence in favor of social interaction effects should be treated with caution, or could even be spurious. Utilizing a parsimonious stochastic model of expectation formation and dynamics, we show that the existing sample sizes of survey expectations are about two orders of magnitude too small to reasonably distinguish between noise and interaction effects. Moreover, we argue that the problem is compounded by the fact that highly correlated responses among agents might not be caused by interaction effects at all, but instead by model-consistent beliefs. Ultimately, these results suggest that existing survey data cannot facilitate our understanding of the process of expectations formation.
Keywords: D84; D85; C83; 330; Survey expectations; model-consistent beliefs; social interaction; networks.